Chickpea antipasto added with Lacticaseibacillus rhamnosus GG: elaboration, characterization and in vitro study of gastrointestinal resistance (Research, Society and Development, 2022)
Functional foods represent one of the most recent trends for the food market due to the concern of consumers, who seek a healthier lifestyle associated with good eating habits. Thus, the objective was to elaborate and characterize a starter of chickpeas added with Lacticaseibacillus rhamnosus GG, and to determine the survival of the probiotic by simulating the gastrointestinal tract (GIT) in vitro. To prepare the antipasto, olive oil, olives, onion, fine herbs, chickpeas and oregano were used. The product was stored at 8°C to carry out physicochemical analyses, viability of the probiotics as well as microbiological quality and survival of the probiotic in the in vitro GIT. The addition of L. rhamnosus GG only altered the antipasti acidity. There was stability of pH, total soluble solids and % of protein in both appetizers (p>0.05) and there was no difference between the color coordinates of the formulations. Probiotic viability remained close to 8.0 Log CFU/g throughout storage. < 1.0 x 10¹ CFU/g of filamentous fungi and Yeasts and Enterobacteriaceae were found. During the in vitro simulation of TGI, the strain presented in the final portion of the intestine (FEII), after eight days of storage, counts close to 4.0 Log CFU/g, guaranteeing 6.0 Log CFU/g, if 100g of the product were consumed. product. The survival rate of L. rhamnosus GG was greater than 54.11%. The probiotic showed excellent viability in the antipasto developed, indicating that the matrix can be further studied and explored regarding the addition of probiotics, due to its promising potential.